The Mediating Role of Knowledge Sharing in the Relationship Between Information Technology and Competitive Advantage: A Study of Its Application in Iraqi Banks - Mohammed Kleban Zuhairi, Mustafa (Indonesian Journal of Business Analytics, 2025)
The current study aims to examine the role of information technology in enhancing the competitive advantage of Iraqi banks through knowledge exchange as a mediator in the relationship. The study sample of 268 employees in distributed across 10 private banks operating in Baghdad. The descriptive analytical approach and structural equation modeling relied on the Smart Pls 3 statistical analysis program. The results generally indicate the importance of information technology and knowledge exchange in enhancing the competitive advantage of institutions. Therefore, institutions should develop a strong technical infrastructure and a corporate culture supporting knowledge exchange to achieve sustainable competitive performance. Banks should increase their efforts to invest strategically in information technology to improve internal operations and enhance competitive capabilities. These investments include upgrading the technical infrastructure and training employees on the use of modern technologies.